Authority and Responsibilities of Tax Consultants in terms of Pmk No. 175/Pmk.01/2022 Regarding Amendment to Financial Regulation Number 111/Pmk.03/2014 Concerning Tax Consultants - Ritonga, Sangap Tua; Rizkia, Nanda Dwi; Fardiansyah, Hardi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted with the aim of analyzing and describing the role of tax advisers in the taxation system in Indonesia and the efforts that can be made to maintain the ethical professionalism of tax advisers as partners of taxpayers and the government. The success of state tax revenue will only be realized if it has the support of all parties, without exception, from the government, tax authorities, to taxpayers and society in general, including tax advisers. The method used in this research is normative legal research. Normative legal research, namely a search based on literature or excavation of documents and library materials or document studies, which is carried out in an effort to obtain the necessary data related to the problem. This type of research is descriptive qualitative research using taxation secondary data from internet research. Qualitative techniques are used in data analysis, with the stages of data collection, data reduction, and inference